2009
DOI: 10.1093/treephys/tpp075
|View full text |Cite
|
Sign up to set email alerts
|

Productivity, water-use efficiency and tolerance to moderate water deficit correlate in 33 poplar genotypes from a Populus deltoides x Populus trichocarpa F1 progeny

Abstract: Genotypic variability for productivity, water-use efficiency and leaf traits in 33 genotypes selected from an F1 progeny of Populus deltoides Bartr. ex Marsh x Populus trichocarpa L. was explored under optimal and moderate water-deficit conditions. Saplings of the 33 genotypes were grown in a two-plot open field at INRA Orléans (France) and coppiced every year. A moderate water deficit was induced during two successive years on one plot by withholding irrigation, while the second one remained irrigated (contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 30 publications
5
48
1
1
Order By: Relevance
“…The average difference in biomass between extreme clones was substantial (about 2.5-fold). Such large variability is documented elsewhere, both at interspecific and intraspecific levels (Monclus et al, 2009), hence reflecting the wide genetic base of the genus (Stettler et al, 1996). Previous results also agree with the observed superiority of 'AF2' over 'Monviso', both clones being specifically bred for biomass although belonging to different taxonomic groups (Mareschi et al, 2005).…”
supporting
confidence: 81%
“…The average difference in biomass between extreme clones was substantial (about 2.5-fold). Such large variability is documented elsewhere, both at interspecific and intraspecific levels (Monclus et al, 2009), hence reflecting the wide genetic base of the genus (Stettler et al, 1996). Previous results also agree with the observed superiority of 'AF2' over 'Monviso', both clones being specifically bred for biomass although belonging to different taxonomic groups (Mareschi et al, 2005).…”
supporting
confidence: 81%
“…Differences in WUE can be identified by differences in carbon isotope ratios in trees, and genotypes with high carbon isotope discrimination (Δ 13 C) have been usually related with higher biomass production and lower WUE (Farquhar, Ehleringer, & Hubick, 1989). However, the occurrence of a significant genotypic variability for productivity and for Δ 13 C (used as a proxy of WUE) in poplars and other tree species has been demonstrated, including a negative relationship between biomass and Δ 13 C (Cassasoli et al., 2004; Guehl, Nguyen‐Queyrens, Loustau, & Ferhi, 1994; Monclus et al., 2009; Zhang, Zang, & Li, 2004) or an opposite pattern (Marron et al., 2005; Rae, Robinson, Street, & Taylor, 2004). WUE in poplars is highly heritable (Monclus et al., 2005, 2006) and there is generally no trade‐off between WUE and productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators in Germany concluded that establishing Populus plantations on a large scale would reduce groundwater recharge [11]. Water use, water use efficiency, and drought resistance vary substantially among hybrid poplar clones [90][91][92], making clone selection an important strategy for minimizing impacts in areas where water is limiting.…”
Section: Water Usementioning
confidence: 99%